2016
DOI: 10.1037/hea0000284
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary experimental examination of worldview verification, perceived racism, and stress reactivity in African Americans.

Abstract: Objective According to worldview verification theory, inconsistencies between lived experiences and worldviews are psychologically threatening. These inconsistencies may be key determinants of stress processes that influence cardiovascular health disparities. This preliminary examination considers how experiencing injustice can affect perceived racism and biological stress reactivity among African Americans. Guided by worldview verification theory, it was hypothesized that responses to receiving an unfair outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 52 publications
5
37
1
Order By: Relevance
“…These variations were fully crossed and simultaneously implemented ten minutes prior to the fourth salivary collection timepoint. A substantive consideration of these manipulations is provided elsewhere (46). Of current interest, hierarchical multiple regressions were also repeated while controlling for both protocol variations to ensure that links between perceived discrimination, racial identity and coordinated biological responses were robust.…”
Section: Resultsmentioning
confidence: 99%
“…These variations were fully crossed and simultaneously implemented ten minutes prior to the fourth salivary collection timepoint. A substantive consideration of these manipulations is provided elsewhere (46). Of current interest, hierarchical multiple regressions were also repeated while controlling for both protocol variations to ensure that links between perceived discrimination, racial identity and coordinated biological responses were robust.…”
Section: Resultsmentioning
confidence: 99%
“…Lucas and colleagues have shown that psychological as well as biological processes that contribute to cardiovascular health disparities are not simply the consequence of individual level exposures but the interplay between individual-level and contextual factors (e.g., views about justice) (63). Mezuk et al have suggested that behaviors may explain why the links between emotional and physical health problems are weaker among Blacks (41).…”
Section: Discussionmentioning
confidence: 99%
“…The Trier Social Stress Test has been shown to activate multiple stress-responsive systems—not only the HPA axis, but also the sympathetic nervous system and immune system (see review by Allen, Kennedy, Cryan, Dinan, & Clarke, 2014)—and thus offers an ideal backdrop against which to study multisystem stress response coordination. Other investigations using this dataset have focused on multisystem coordination during discrete phases of the stress response and associations with perceived discrimination and racial identity (Lucas et al, under review), and how different aspects of the stress response relate to fit between justice beliefs and experienced injustice (Lucas et al, 2016). By contrast, the current study examines different levels of pairwise coordination among stress systems (i.e., within-person matched phase coordination and between-person differences in average level coordination) and probes the consequences of such coordination by relating individual differences in temporal coordination to post-stress appraisals and affect.…”
Section: Relations With Subjective Stressmentioning
confidence: 99%